Communication in teams - an expression of social conflicts - Klünder, Jil; Schneider, Kurt; Kortum, Fabian; Straube, Julia; Handke, Lisa; Kauffeld, Simone (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2016)
The more members a team has, the more information needs to be shared with single team members or within the whole team. Sufficient information sharing is difficult to ensure, since a project leader will not be fully aware of all on-going information and communication within the team. In software engineering, information flow is essential for project success. In each part of the process, information like requirements or design decisions needs to be communicated with appropriate persons. Neither missing nor wrong implemented requirements are desirable, since extra working hours or incomplete working results need to be paid. Therefore, the right amount of information sharing is highly desirable. To ensure this, communication is a mandatory requisite. Furthermore, knowing about social conflicts is suitable, since these influence the information flow. In an experiment with 34 student software projects, we collected data referring to internal team communication and mood. In these projects, we could show a correlation between chosen communication channels, social conflicts and mood. Since social conflicts foster an insufficient information flow, knowing about these helps software developing teams to reach higher quality and a higher customer satisfaction.
CRIS-Team Scopus Importer:2023-09-18